1996
DOI: 10.1021/ic960772p
|View full text |Cite
|
Sign up to set email alerts
|

NMR Investigation of β-Substituted High-Spin and Low-Spin Iron(III) Tetraphenylporphyrins

Abstract: The NMR spectra of a series of beta-substituted iron(III) tetraphenylporphyrin (2-X-TPP) complexes have been studied to elucidate the relationship between the electron donating/withdrawing properties of the 2-substituent and the (1)H NMR spectral pattern. The electronic nature of the substituent has been significantly varied and covered the -0.6 to 0.8 Hammett constant range. Both high-spin and low-spin complexes of the general formula (2-X-TPP)Fe(III)Cl and [(2-X-TPP)Fe(III)(CN)(2)](-) have been investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 74 publications
5
67
0
Order By: Relevance
“…[14] Actually, the variation of the β-H positions in the 1 H NMR spectrum may be accounted for by specific π-delocalization mechanisms that have been discussed in detail for iron(III) porphyrins. [96,97] One pyrrole 3-H and the 2-NH resonance are evidently different from the other six and show upfield shifts. Thus, the side-on locawww.eurjic.orgtion of the iron(II) with respect to the pyrrole ring primarily affects spin transfer to the modified pyrrole ring.…”
Section: Thementioning
confidence: 95%
See 1 more Smart Citation
“…[14] Actually, the variation of the β-H positions in the 1 H NMR spectrum may be accounted for by specific π-delocalization mechanisms that have been discussed in detail for iron(III) porphyrins. [96,97] One pyrrole 3-H and the 2-NH resonance are evidently different from the other six and show upfield shifts. Thus, the side-on locawww.eurjic.orgtion of the iron(II) with respect to the pyrrole ring primarily affects spin transfer to the modified pyrrole ring.…”
Section: Thementioning
confidence: 95%
“…meric form, [111] and in the oxidation of [(HCPH)Ni II ] with OsO 4 . [112] Selected spectra that emphasize the utility of 1 [7] iron(III) β-substituted tetraarylporphyrin, [96] and iron(III) N-methyltetraarylporphyrin (δ av for regular pyrrole rings), [13] and the average chemical shift of [(HCPH)Fe…”
Section: Reaction Of [(Hcph)fementioning
confidence: 99%
“…The relative intensities of the resonances and the COSY spectrum allowed the assignment of all the protons except for the two meso protons, α and γ, and the β-pyrrole protons. It was previously reported that HMQC spectroscopy of paramagnetic iron porphyrins provides the scalar heterocorrelation under natural abundance conditions of 13 C. [11] In the present study, this correlation technique offers a route to identify the β-pyrrole resonances by taking advantage of the fact that the full assignment of the proton signals of the β-13 C-1 H pairs has been established. Thus, the signal assignment of the carbons with directly bonded protons such as β-pyrrole protons and meso protons ( 13 C-1 H) was done on the basis of HMQC experiments.…”
Section: Low-spin Complexesmentioning
confidence: 86%
“…The 1 H NMR spectra reflect features typical for low-spin (porphyrin)iron(III) complexes. [31,56] ester, and protoporphyrin-IX dimethyl ester, respectively). [22,26,46] Based on the chemical shifts measured for the four (deuterooxophlorin)iron isomers [(DeuteroPO)Fe(py) 2 ], the following values are anticipated for (5-oxophlorin)iron or its β-methylated derivative: pyrrole resonances: δ ϭ Ϫ33 (2-H), 27 (3-H), 13 (12-and 13-H) ppm; methyl resonances: δ ϭ 65 (2-CH 3 ), Ϫ14 (3-CH 3 ) ppm.…”
Section: Electronic Structure Of [(5-o-trpp)fe(py) 2 ] and [(5-otrpp)mentioning
confidence: 99%
“…Additionally, the π delocalization locates a considerable amount of the spin density at the meso positions, [16,31,53Ϫ55] and some at the pyrrole positions. [56] The π-spin density at the meso-carbon atoms produces sign alternation of the meso-phenyl resonances. The dipolar contribution, caused only by the ZFS effect in high-spin (porphyrin)iron complexes, is usually notably smaller than the contact contribution, and this observation has been applied in the further analysis of the hyperfine shifts.…”
Section: H Nmr Spectroscopic Studies Of [(5-o-trpp)fe III ]mentioning
confidence: 99%